Key Updates in the WADA 2025 Prohibited List: Implications for Competitive Sports - Michalik, Maciej; Lorenc, Tomasz; Muras, Mateusz; Marcinkowski, Krzysztof; Mikszta, Natalia; Mikszta, Jakub; Marcinkowska, Julia (Quality in Sport, 2025)
The 2025 revision of the World Anti-Doping Agency (WADA) Prohibited List introduces significant updates grounded in recent pharmacological developments, emerging therapeutic compounds, and shifting patterns of misuse in sport. This scientific brief outlines key changes, including the addition of novel agents such as ryanodine receptor-1-calstabin complex stabilizers (e.g., S-107, ARM210) to the S0 category, the estrogen receptor degrader elacestrant to S4.2, and MOTS-c to the metabolic modulators section (S4.4). Other revisions include formal recognition of insulin mimetics (S519, S597), the naming of xipamide as a masking agent, and stricter dosing intervals for inhaled formoterol. Classification updates affect stimulants such as hydrafinil (reallocated to S6.A), and newly listed specified stimulants including midodrine and tesofensine. The revised policy also clarifies the permissibility of blood donation via apheresis procedure under strict oversight and introduces notable sport-specific changes, which is removal of β-blockers from the Prohibited List for selected skiing and snowboarding disciplines, following recommendations by the International Ski Federation (FIS). These changes underscore WADA’s commitment to preemptive regulation based on emerging risks, ensuring fairness and athlete safety. Where applicable, clinical rationale, therapeutic use implications, and detection methodologies are discussed to support implementation and compliance across sports.